Successful Management of the Response to the COVID-19 Pandemic in the Bangkok Metropolitan Administration - Matanee Radabutr; Jureerat Kijsomporn; Payao Phongsakchat; Kanjana Anutariya (Journal of Health Science and Medical Research, 2026)
Objective: This research aimed to study the successful management of the response to the COVID-19 pandemic in the Bangkok Metropolitan Administration. Material and Methods: A mixed-methods convergent design was conducted. The qualitative component involved 30 semi-structured interviews with healthcare providers from three public health service centers in the Bangkok Metropolitan Administration, using seven open-ended questions until data saturation was reached. The quantitative sample, based on G*Power analysis, comprised 300 healthcare providers who were willing to complete informed consent forms and online questionnaires comprising three sections. Qualitative data were analyzed using thematic analysis, and quantitative data were analyzed using descriptive statistics. Data convergence was achieved through joint display matrices. Results: The convergent mixed-methods research findings demonstrated alignment between the qualitative and quantitative data. The convergent mixed-methods analysis integrated qualitative and quantitative findings through joint presentations, indicating four key factors: (1) the customized policy frameworks for contextual implementation; (2) optimizing human capital through enhanced resource allocation; (3) the development of community integrated operational pathways to complete the care continuum; and (4) the enhancement of system capacity to improve discharge experience and staff welfare. Conclusion: The response to the COVID-19 pandemic was characterized by a control structure that excelled at issuing broad directives but failed to address the resource allocation and human welfare aspects of pandemic management. Therefore, guidelines for formulating management strategies for emerging infectious diseases may facilitate their sustainability across future pandemics while maintaining compassion, equity, and resilience within the community.